Analisis Pendapatan dan Adopsi Usaha Tani Padi Organik dan Anorganik di Desa Cibatu Kecamatan Cikembar Kabupaten Sukabumi: Analysis of Income and Adoption of Organic and Inorganic Rice Farming in Cibatu Village, Cikembar District, Sukabumi Regency - Yulianti, Yuli; Hardjanto, Arini (IPB University, 2025)
The agricultural sector plays a strategic role in the economy and food supply for the community. The implementation of the green revolution program aimed at increasing production has resulted in environmental impacts and dependence on chemical inputs. As a sustainable alternative, organic farming systems have been implemented, one of which is in Cibatu Village, West Java. However, the adoption rate is still relatively low, with only 30% of farmers having switched to organic farming. The obstacles faced are high labor requirements, difficult market access, and minimal information regarding the potential and benefits of organic farming systems. This study aims to (1) estimate the income of organic and inorganic rice farming businesses and (2) analyze the factors influencing the adoption of organic and inorganic rice farming businesses. Data analysis used includes income analysis and R/C ratio, as well as logistic regression analysis. The results show that the ratio of income to total costs in organic rice farming is higher, namely Rp 9,892,069 and inorganic rice Rp 7,186,011. The R/C ratio to total farming costs for organic rice is 1.45% higher than for inorganic rice, which is 1.34%. Logistic regression analysis shows that farm income significantly influences farmers' decisions to adopt organic rice, while farming experience and productivity do not. Sektor pertanian memiliki peran strategis dalam perekonomian dan penyediaan pangan masyarakat. Penerapan program revolusi hijau yang ditujukan untuk meningkatkan produksi justru menimbulkan dampak lingkungan serta ketergantungan terhadap input kimia. Sebagai alternatif keberlanjutan, sistem pertanian organik telah diterapkan, salah satunya di Desa Cibatu, Jawa Barat. Namun tingkat adopsi masih tergolong rendah baru mencapai 30% petani yang beralih ke pertanian organik. Hambatan yang dihadapi yaitu kebutuhan tenaga kerja yang tinggi, kesulitan akses pasar, dan minimnya informasi tentang potensi serta keuntungan sistem pertanian organik. Penelitian ini bertujuan untuk (1) mengestimasi pendapatan usaha tani padi organik dan anorganik dan (2) menganalisis faktor-faktor adopsi usaha tani padi organik dan anorganik. Analisis data yang digunakan yaitu analisis pendapatan dan R/C ratio, serta analisis regresi logistik. Hasil menunjukkan bahwa pendapatan atas biaya total pada usaha tani padi organik lebih besar yaitu Rp 9.892.069 dan padi anorganik Rp 7.186.011. R/C ratio atas biaya total usaha tani padi organik lebih tinggi sebesar 1,45 dibandingkan padi anorganik sebesar 1,34. Analisis regresi logistik menunjukkan variabel pendapatan usaha tani berpengaruh signifikan terhadap keputusan petani dalam mengadopsi padi organik, sementara pengalaman berusaha tani dan produktivitas tidak berpengaruh signifikan.